2006
DOI: 10.1093/nar/gkl982
|View full text |Cite
|
Sign up to set email alerts
|

Insect small nuclear RNA gene promoters evolve rapidly yet retain conserved features involved in determining promoter activity and RNA polymerase specificity

Abstract: In animals, most small nuclear RNAs (snRNAs) are synthesized by RNA polymerase II (Pol II), but U6 snRNA is synthesized by RNA polymerase III (Pol III). In Drosophila melanogaster, the promoters for the Pol II-transcribed snRNA genes consist of ∼21 bp PSEA and ∼8 bp PSEB. U6 genes utilize a PSEA but have a TATA box instead of the PSEB. The PSEAs of the two classes of genes bind the same protein complex, DmSNAPc. However, the PSEAs that recruit Pol II and Pol III differ in sequence at a few nucleotide positions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 52 publications
1
72
0
Order By: Relevance
“…Like their vertebrate counterparts, snRNA promoters in Drosophila contain highly conserved elements not present in other Drosophila genes (17,25,34). To test whether Drosophila snRNA promoters are also necessary for correct 3Ј-end formation, as they are in vertebrates (6,20), we removed the U7 snRNA promoter and replaced it with the actin 5C promoter, which normally drives the synthesis of a polyadenylated mRNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like their vertebrate counterparts, snRNA promoters in Drosophila contain highly conserved elements not present in other Drosophila genes (17,25,34). To test whether Drosophila snRNA promoters are also necessary for correct 3Ј-end formation, as they are in vertebrates (6,20), we removed the U7 snRNA promoter and replaced it with the actin 5C promoter, which normally drives the synthesis of a polyadenylated mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…4C). The Drosophila snRNA promoters are distinct from the promoters of RNAPII-transcribed mRNAs (17), and the coupling of snRNA promoters to 3Ј-end formation observed for vertebrate spliceosomal snRNAs is conserved for Drosophila U7 snRNA 3Ј-end formation. This indicates that the 3Ј-end formation mechanism was already present early in metazoan evolution; this is supported by the observation of orthologues of Integrator subunits encoded in several plant genomes.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the structural and sequence similarities between dMRP RNA and MRP RNAs in other species described by Piccinelli et al (2005), we identified genomic sequences flanking dMRP RNA resembling RNA Pol III regulatory elements ( Fig. 1; Hernandez et al 2007). The presence of these elements suggests that in Drosophila, as in most species, FIGURE 6.…”
Section: Drosophila Mrp Rna Is Orthologous To Mrp Rna Genes In Other mentioning
confidence: 65%
“…Positions of PSE (À44 nt) and TATA-like element (À23 nt) upstream of the transcription start site (+1) are indicated above the sequence. (Green nucleotides in promoter elements) Identical nucleotides in all reference sequences (Hernandez et al 2007), (blue nucleotides) the same as at least one of the reference sequences, (red nucleotides) consensus Pol III terminator (Hernandez et al 2007). observed in S2 cells (data not shown). Nucleolar localization of dMRP RNA suggests that this is a conserved feature of MRP RNA.…”
Section: Resultsmentioning
confidence: 83%
“…We generated various gRNAs targeting the yellow body color gene, using two endogenous Drosophila U6 promoters, dU6-2 and dU6-3 (Wakiyama et al 2005;Hernandez et al 2007) (Figure S2A). We identified dU6-3 as a more potent gRNA promoter based on somatic mutation of yellow with act5C-Cas9 ( Figure S2B).…”
Section: Resultsmentioning
confidence: 99%